1993
DOI: 10.1051/lait:199314
|View full text |Cite
|
Sign up to set email alerts
|

Growth-promoting activity of tryptic digest of caseinomacropeptide for Lactococcus lactis subsp lactis

Abstract: Summary -Tryptic digest of caseinomacropeptide (e-terminal part of x-caseln) was separated into 2 fractions by ultrafiltration membrane (eut-off point 3 000 Da). Both fractions strongly stimulated, in a dose-response-dependent manner, Lactococcus lactis subsp lactis CNRZ 1076 growth in reconstituted skim milk. Growth rates were 2-fold higher than that observed in the control culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 14 publications
1
13
0
Order By: Relevance
“…On the other hand, two fractions with different molecular mass profiles, separated by ultrafiltration (3 kDa cut-off) from a tryptic hydrolysate of CMP, stimulated growth of Lactococcus lactis subsp. lactis in reconstituted skim milk in a dose-dependent manner (Bouhallab, Favrot, & Maubois, 1993).…”
Section: Health Effects Of Cmp-derived Peptidesmentioning
confidence: 99%
“…On the other hand, two fractions with different molecular mass profiles, separated by ultrafiltration (3 kDa cut-off) from a tryptic hydrolysate of CMP, stimulated growth of Lactococcus lactis subsp. lactis in reconstituted skim milk in a dose-dependent manner (Bouhallab, Favrot, & Maubois, 1993).…”
Section: Health Effects Of Cmp-derived Peptidesmentioning
confidence: 99%
“…These authors suggested that disulfide/sulphydryl residues of ic-casein in combination with another tryptic peptide are required for growth of some species of bifidobacteria. Recently, Bouhallab et al (1993) noted that tryptic digest of caseinomacropeptide separated into two fractions by UF stimulated the growth and acid production of Lactococcus /actis subsp lactis in skim milk.…”
Section: Cinétiques De Croissance De B Infantis (A D) B Breve (B Ementioning
confidence: 99%
“…The types of peptides found in MP fraction from tryptic hydrolyzates stimulated the growth of bifidobacteria in a dose-response de pendent manner (Bouhallab et al, 1993). However, the length of peptides and amino acid content of casein fractions could lead to growth inhibition.…”
Section: Cinétiques De Croissance De B Infantis (A D) B Breve (B Ementioning
confidence: 99%
“…It is thought to inhibit the adhesion of various bacteria, viruses and toxins, including Helicobacter pylori and rotavirus, to the cell membrane by binding to the pathogen's receptor sites (Kawakami 1997). In vitro assays also showed that GMP strongly promoted the growth of Bifidobacterium breve , B. bifidum B. infantis as well as Lactococcus lactis (Bouhallab et al. 1993; Idota et al.…”
Section: Introductionmentioning
confidence: 97%